К вопросу оценки эффективности перехода к двухтрубной системе теплоснабжения - Алексахин, Александр Алексеевич; Ена, Светлана Васильевна; Гордиенко, Елена Петровна; Ландар, А. А.; Бурда, О. С. (НТУ "ХПИ", 2016)
Запропоновано формули для визначення площі поверхні теплопередачі і витрат мережної води при переході від чотиритрубної системи теплопостачання мікрорайону до двотрубної. Формули отримано при умові, що у вихідному варіанті теплообмінники гарячого постачання приєднано до теплових мереж за двоступінчастою послідовною схемою. На прикладі ідеалізованих груп житлових будівель проведено оцінки впливу кількості мешканців на зміну площі теплопередачі і витрат теплоносія.

The formulas have been proposed to determine the changes of heat transfer surface area and heat-system water consumption while four-pipe district heating system has been changed into two-pipe heating system. The formulas have been obtained under the condition that originally hot water supplying system heat exchangers and heating nets were connected by two-stage series scheme. The influence of district population on changes of heat transfer surface area and heat-system water consumption has been investigated taking into consideration idealized groups of residential buildings.
On evaluation of efficiency of heat supply system changing into two-pipe system
Keywords: водонагревательная установка; ВНУ; сетевая вода; подогреватель; теплопередача